2003
DOI: 10.1016/s0169-555x(02)00167-8
|View full text |Cite
|
Sign up to set email alerts
|

River response to an active fold-and-thrust belt in a convergent margin setting, North Island, New Zealand

Abstract: High-resolution digital elevation data (TOPSAR 10-m grid) are used to reconstruct Late Quaternary growth histories of subtle folding in the Wairarapa fold-and-thrust belt, North Island, New Zealand. Outcrop data of deformed latest Miocene and younger strata are combined with observations of warped and faulted late Quaternary terrace surfaces to unravel the geomorphic and structural history of the Huangarua River valley. Optically stimulated luminescence (OSL) dating of loess that accumulated on these strath te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 47 publications
(93 reference statements)
2
37
0
Order By: Relevance
“…In erosional settings such as high mountains, fluvial terraces above a modern river record periods of fluvial stability that interrupt prevalent incision (e.g., Vandenberghe et al, 2011). The factors behind changes in the fluvial dynamic associated with sediment deposition, terrace abandonment and subsequent incision may be complex because of the interplay of tectonics and climate (e.g., Pazzaglia et al, 1998;Burbank and Anderson, 2001;Formento-Trigilio et al, 2002;Pan et al, 2009). Globally compiled fluvial records indicate that terrace formation is primarily a consequence of tectonic uplift combined with cyclic climate (e.g., Bridgland and Westaway, 2008;Westaway et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In erosional settings such as high mountains, fluvial terraces above a modern river record periods of fluvial stability that interrupt prevalent incision (e.g., Vandenberghe et al, 2011). The factors behind changes in the fluvial dynamic associated with sediment deposition, terrace abandonment and subsequent incision may be complex because of the interplay of tectonics and climate (e.g., Pazzaglia et al, 1998;Burbank and Anderson, 2001;Formento-Trigilio et al, 2002;Pan et al, 2009). Globally compiled fluvial records indicate that terrace formation is primarily a consequence of tectonic uplift combined with cyclic climate (e.g., Bridgland and Westaway, 2008;Westaway et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite Fig. IB and C only showing one set of alluvial fans (Q4a), field investigations indicated that within some of the gullies incised into the fans, lower fan surfaces are preserved (see also Formento-Trigilio et al 2003). Approximately 100 m southeast of the foot of the fold-scarp, a stream flows southwest (Fig.…”
Section: Morphology Of the Active Tracementioning
confidence: 96%
“…2. In profile E-E , the unevenness of topography on the footwall side makes interpretation difficult, but the maximum vertical separation is inferred to be c. 1.7 m. faN aND terrace ageS Age constraints for the deformed alluvial fans (Q4a) and little deformed fluvial terraces (Q2a) are provided by OSL ages reported by Formento-Trigilio et al (2003). The location of the two OSL sample sites closest to the Martinborough Fault are shown on Fig.…”
Section: Vertical Separation On Q4a Fansmentioning
confidence: 99%
See 1 more Smart Citation
“…The Waiohine terrace is regarded as equivalent to the Ohakean terrace, both surface and fill, elsewhere in the North Island (Palmer 1984). The age of aggradation, cessation of aggradation and subsequent abandonment of the Ohakean (0Waiohine) terrace has been the subject of a good deal of recent investigation (Formento-Trigilio et al 2003;Litchfield & Berryman 2005;Wang & Grapes 2008;Carne et al 2011; see also references cited therein). Litchfield & Berryman (2005) interpret the timing of abandonment of the Ohakean terrace in the three largest catchments in southeastern North Island to be 15Á20 ka.…”
Section: Waiohine Surface Agementioning
confidence: 99%